Thermodynamic analysis of an existing coal-fired power plant for district heating/cooling application - Erdem, Hasan Huseyin; Dagdas, Ahmet; Sevilgen, Suleyman Hakan; Cetin, Burhanettin; Akkaya, Ali Volkan; Sahin, Bahri; Teke, Ismail; Gungor, Cengiz; Atas, Selcuk (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
In a conventional coal-fired power plant, which is only designed for electricity generation, 2/3 of fuel energy is wasted through stack gases and cooling water of condensers. This waste energy could be recovered by trigeneration; modifying the plants in order to meet district heating/cooling demand of the locations. In this paper, thermodynamical analysis of trigeneration conversion of a public coal-fired power plant, which is designed only for electricity generation, has been carried out. Waste heat potential and other heat extraction capabilities have been evaluated. Best effective steam extraction point for district heating/cooling system; have been identified by conducting energetic and exergetic performance analyses. Analyses results revealed that the low-pressure turbine inlet stage is the most convenient point for steam extraction for the plant analyzed. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Power plant modification; Cogeneration; Exergy; Energy; Waste heat; Thermodynamics; Energy & Fuels; Engineering; Mechanics